Combined education and patient-led goal setting intervention reduced chronic low back pain disability and intensity at 12 months: a randomised controlled trial. Issue 22 (26th February 2019) - Gardner, Tania; Refshauge, Kathryn; McAuley, James; Hübscher, Markus; Goodall, Stephen; Smith, Lorraine
Abstract : Background: One model of care that has not been tested for chronic low back pain (LBP) is patient-led goal setting. We aimed to compare the clinical effectiveness and healthcare use of a patient-led goal setting approach (intervention) with simple advice to exercise (control) over 12 months. Methods: An assessor-blinded randomised controlled trial. Intervention was education combined with patient-led goal setting compared with a control group receiving a standardised exercise programme. The primary outcomes were back pain disability and pain intensity. Secondary outcomes were quality of life, kinesiophobia, self-efficacy, depression, anxiety and stress. Outcomes and healthcare use were assessed immediately post-treatment (2 months) and after 4 and 12 months. Analysis was by intention to treat. Results: Seventy-five patients were randomly assigned to either the intervention (n=37) or the control (n=38) group. Using linear mixed model analyses, adjusted mean changes in primary outcomes of disability and pain intensity were greater in the intervention group than in the control group (disability post-treatment: p<0.05). These differences were clinically meaningful. Mean differences in all secondary measures were greater in the intervention group than in the control group (p<0.05). There was no difference in healthcare use between groups over 12 months. Conclusion: A patient-led goal setting intervention was significantly more effective than advice to exercise for improving outcomes in disability, pain intensity, quality of life, self-efficacy and kinesiophobia in chronic LBP. These improvements were maintained at 12 months. Smaller effects were seen in measures of depression, anxiety and stress. Trial registration number: ACTRN12614000830695.